Code Switching as Seen in Trading (A Sociolinguistic Studies Field Research) - Oriza Agustin; Vera Magria; Leny Setiyana (Journal of Foreign Language Teaching and Learning, 2020)
This research aims to describe code-switching, as seen in trading activity in Kota Solok. The objectives of this writing are to identify the form of codes which are commonly used by bilingual and diglossic inhabitants in trading activity in Solok market, to classify the code-switching which happens when the sellers and the buyers are talking to each other and to find out the factors which caused code-switching and diglossia. This research applied descriptive qualitative research in which the data came from a conversation in trading activities in Kota Solok. The data were also from the informants' statements about the things, which were related to the coding problem itself. The researcher collected the observational method supported by note-taking and recording techniques. The result found that there were several forms of code-switching in trading activity in the Kota Solok market: the switching among language codes among dialect codes and various codes. The diglossic situation also existed in society. The diglossic situation could emerge when society had two languages, while each showed different functions (high and low) in a different community. It could be seen in the Merantau tradition by Minang People.